1997
DOI: 10.1021/ja962381f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Electronic Spectrum of Plastocyanin

Abstract: The electronic spectrum of the blue copper protein plastocyanin has been studied by ab initio multiconfigurational second-order perturbation theory (the CASPT2 method). The six lowest electronic transitions have been calculated and assigned with an error of less than 2000 cm-1. The singly occupied orbital in the ground state is Cu 3d−SCys 3pπ antibonding with some NHis 2pσ character. The bright blue color originates from an electron transfer to this orbital from the corresponding Cu 3d−SCys 3pπ bonding orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
200
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(217 citation statements)
references
References 31 publications
17
200
0
Order By: Relevance
“…The intense band arises from an excitation from the bonding combination of the Cu 3d x 2 y 2 orbital and the S cys 3p p orbital to the SOMO. [5][6][7] Closely related blue copper sites, such as cucumber basic protein, pseudoazurin and nitrite reductase, each have a slightly distorted active site compared to plastocyanin and exhibit remarkably different spectral features, in particular an increased intensity of the higher energy band. 4,8 Furthermore, recent studies have shown that a closely related protein, nitrosocyanin, adsorbs in the red.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intense band arises from an excitation from the bonding combination of the Cu 3d x 2 y 2 orbital and the S cys 3p p orbital to the SOMO. [5][6][7] Closely related blue copper sites, such as cucumber basic protein, pseudoazurin and nitrite reductase, each have a slightly distorted active site compared to plastocyanin and exhibit remarkably different spectral features, in particular an increased intensity of the higher energy band. 4,8 Furthermore, recent studies have shown that a closely related protein, nitrosocyanin, adsorbs in the red.…”
Section: Introductionmentioning
confidence: 99%
“…7,[14][15][16][17][18][19][20] However, there has been less attention on small molecules that incorporate the copper-cysteine bond. Ryde et al have studied the structure and reorganization energy of small models of the copper cysteine bond, including CuSH 0/+ and [Cu(imidazole-CH 3 ) 2 (SC 2 H 5 (CH 3 SC 2 H 5 )] 0/+ , using a number of theoretical methods including density functional theory (DFT) with the B3LYP exchange-correlation functional, perturbation theory and coupled cluster theory.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of the blue copper site of plastocyanin has been studied extensively during the last decades both by experimental approaches (5,16,17,38) and quantum chemical calculations (5,10,(25)(26)(27)47). It was found that the unpaired electron spin density is located predominately at the atomic orbitals of the four atoms in the trigonal NNS-plane, i.e., the copper atom, the Cys S ␥ ligand, and the two aromatic His N ␦ ligands (5,16,17,(25)(26)(27)30), whereas the electron spin density at the Met S ␦ atom and the Cys H ␤ is small (26)(27)(28)38). Yet, it was found recently (31) that also the latter orbitals must be included in the description of the unpaired electron spin density to obtain a reliable prediction of the paramagnetic relaxation of the protons close to the copper site.…”
Section: Distribution Of the Unpaired Electron Spin In Plastocyaninmentioning
confidence: 99%
“…Because the paramagnetic restraints are derived from the relaxation rates of nuclei close to the metal site, the point dipole approximation of the electron spin fails and a description of the paramagnetic relaxation that takes the electron delocalization into account must be used (37). Therefore, the approach requires knowledge of the distribution of the unpaired electron spin, which can be obtained experimentally by x-ray absorption spectroscopy (16, 17), electron nuclear double resonance (38), paramagnetic NMR (28-31) spectroscopy, or theoretically by quantum chemical calculations (5,(25)(26)(27). The blue copper protein, plastocyanin from Anabaena variabilis (A.v.…”
mentioning
confidence: 99%
See 1 more Smart Citation